Gambaran Pelaksanaan Pembelajaran Keterampilan Menjahit Pakaian di PKBM - Kasari, Dwi Yanti Masvi; Syuraini, Syuraini (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The research was based on the success of the sewing clothes’ skill program in PKBM Anarvani Air Tawar Barat, Padang city. The existence of the implementation in sewing clothes skill learning, it could help the participant in developing its skill, can be shown from the result that has been reached. The researcher expected the cause of the success of sewing clothes’ skill was from the learning process. The aim of this research is to show the learning motivation and the atmosphere of study. This research was descriptive quantitative. The population of the research is the entire participant who enrolled in sewing clothes’ program, 20 people as the sample. The technique used in getting the sample was the census method. The technique used in collecting data was using a questionnaire and the equipment to collect the data was using the question’s list. The result of the research is, 1. the motivation of learning that has done by the tutor to push the spirit of the participant is categorized best. 2. the atmosphere of learning study between the tutor and participant is categorized best made the implementation of learning could run well and evoked the comfortableness for the participant.